Ontological approach in improving Islamic economic literacy - Wiraputra, Jhody; Andriani, Yulia; Pratiwi, Palupi; Safira, Isti; Madnasir, Madnasir; Ghofur, Ruslan Abdul (Priviet Social Sciences Journal, 2025)
This study examines the role of the ontology approach in enhancing Islamic economic literacy in Indonesia, a strategic effort given the country's low national Sharia Financial Literacy Index, which stood at 43.42% in 2025. Ontology, as a philosophical study of the nature of existence, became the foundation for defining Islamic economics not only as a social science but also as an integral part of Tawheed, in which all economic activity is seen as a mandate from Allah and aims to achieve Falah. This ontological approach is vital because the nature of Islamic Economics is derived from divine revelation, in contrast to conventional economics, which is derived from human thought. Without a deep understanding of this ontological nature, such as the fundamental difference between usury and profit sharing, people tend to equate Shariah products with conventional ones, differing only in their labels. Using a literature study and philosophical content analysis, the study concludes that ontological understanding serves as an epistemological filter that encourages critical thinking, allowing literate individuals to distinguish between renaming and changing the essence. Therefore, ontological integration transforms literacy from surface normative compliance into an authentic systemic and philosophical understanding, which is essential for constructing a just and sustainable Islamic economic system.